Visceral Leishmaniasis IgG1 Rapid Monitoring of Cure vs. Relapse, and Potential for Diagnosis of Post Kala-Azar Dermal Leishmaniasis - Marlais, Tegwen; Bhattacharyya, Tapan; Singh, Om Prakash; Mertens, Pascal; Gilleman, Quentin; Thunissen, Caroline; Hinckel, Bruno C. Bremer; Pearson, Callum; Gardner, Bathsheba L.; Airs, Stephanie; de la Roche, Marianne; Hayes, Kiera; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
Background: There is a recognised need for an improved diagnostic test to assess post-chemotherapeutic treatment outcome in visceral leishmaniasis (VL) and to diagnose post kala-azar dermal leishmaniasis (PKDL). We previously demonstrated by ELISA and a prototype novel rapid diagnostic test (RDT), that high anti-Leishmania IgG1 is associated with post-treatment relapse versus cure in VL. Methodology: Here, we further evaluate this novel, low-cost RDT, named VL Sero K-SeT, and ELISA for monitoring IgG1 levels in VL patients after treatment. IgG1 levels against L. donovani lysate were determined. We applied these assays to Indian sera from cured VL at 6 months post treatment as well as to relapse and PKDL patients. Sudanese sera from pre- and post-treatment and relapse were also tested. Results: Of 104 paired Indian sera taken before and after treatment for VL, when deemed clinically cured, 81 (77.9%) were positive by VL Sero K-SeT before treatment; by 6 months, 68 of these 81 (84.0%) had a negative or reduced RDT test line intensity. ELISAs differed in positivity rate between pre- and post-treatment (p = 0.0162). Twenty eight of 33 (84.8%) Indian samples taken at diagnosis of relapse were RDT positive. A comparison of Indian VL Sero K-SeT data from patients deemed cured and relapsed confirmed that there was a significant difference (p < 0.0001) in positivity rate for the two groups using this RDT. Ten of 17 (58.8%) Sudanese sera went from positive to negative or decreased VL Sero K-SeT at the end of 11-30 days of treatment. Forty nine of 63 (77.8%) PKDL samples from India were positive by VL Sero K-SeT. Conclusion: We have further shown the relevance of IgG1 in determining clinical status in VL patients. A positive VL Sero K-SeT may also be helpful in supporting diagnosis of PKDL. With further refinement, such as the use of specific antigens, the VL Sero K-SeT and/or IgG1 ELISA may be adjuncts to current VL control programmes.